Investigation on the current situation of research and development capacity of ICU specialist nurses in Guangxi, China (广西壮族自治区ICU专科护士科研和发展能力现状调查) - HUANG Yingqiong (黄映琼); JIANG Li (蒋莉); TIAN Weiyi (田韦毅); MO Jinli (莫金莉); ZHANG Yun (张云); NING Chuanyi (宁传艺) (中西医结合护理)
Objective To understand the current situation of research level and development ability of ICU specialist nurses in Guangxi, China, and to provide a reference basis for further improving the use and training of ICU specialist nurses. Methods A cross-sectional survey was conducted using a self-made structured questionnaire on the specialist nurses who obtained the ICU specialist nurse certification in Guangxi from 2010 to 2022. Results A total of 192 ICU specialist nurses were surveyed, 122 (63. 54%) had published papers, 45 (23. 44%) were the leading researcher of the project, 77 (40. 10%) had obtained patents; 51 (26. 56%) had participated in consultations, and 133 (69. 27%) had obtained specialist nurse certificates and then attended continuing education training. There were statistical differences in scientific achievements, participation in consultation and continuing education among specialist nurses with different titles, positions and working ages (P<0. 05). Conclusion The scientific research ability of Guangxi ICU specialist nurses is at a medium level, and there is still room for upward development. Hospitals should clarify job responsibilities and improve the relevant management system to promote the professional development of specialist nurses. (目的 了解广西壮族自治区(以下简称“广西”)ICU专科护士科研水平和发展能力现状, 为进一步完善ICU专科护士的使用与培养提供参考依据。方法 采用自制结构式问卷对2010年—2022年广西取得ICU专科护士证书的专科护士进行横断面调查。结果 共调查192名ICU专科护士, 122(63. 54%)人发表了论文, 45(23. 44%)人主持了课题, 77(40. 10%)人取得过专利; 51(26. 56%)人参与过会诊, 133(69. 27%)人取得专科护士证书后参加继续教育培训。不同职称、职务和工作年龄的专科护士在科研成果、参与会诊和继续教育情况方面差异有统计学意义(P<0. 05)。结论 广西ICU专科护士科研能力处于中等水平, 专科护理发展能力仍有上升空间, 医院应明确岗位职责, 完善相关管理制度, 促进专科护士职业发展。)